EFEKTIVITAS PENGGUNAAN MEDIA VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR SOSIOLOGI SISWA KELAS XI IPS SMA ISLAMIYAH PONTIANAK - Sakila, Sahala Qaulan; Rustiyarso, Rustiyarso; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the condition of the learning process that is not optimal so that it influences student learning outcomes. This study aims to find out how the use of learning video media, how student learning outcomes after the use of media, and how effective the use of media in class XI IPS Islamiyah Senior High School Pontianak. This research was conducted with a quantitative approach and method quasi experimental research. The sample in this study were all students of class XI IPS as participants who filled out test questions on the material of multicultural society. Before conducting data collection, instrument analysis was first carried out to sociologists and media experts. After that, the results of the research data were analyzed by analysis of learning outcomes and effectiveness analysis to find out how the use of learning video media, learning outcomes after using it, and the effectiveness of the media. The results of the analysis show that: 1) video media makes students interact with each other about the videos that have been watched, confidently express examples through the videos they watch, and not fixated on memorization when answering questions from teachers, 2) experimental class learning outcomes have an average value 73.33 with completeness as many as 17 people, and the control class has an average value of 56.85 with completeness as many as 10 people, 3) the results of the test Effect Size shows that the effectiveness of this media is 0.7425 which can be classified as moderate.Â Keywords: Use of learning video media, student learning outcomes